2013
DOI: 10.1111/1574-6968.12119
|View full text |Cite
|
Sign up to set email alerts
|

The leafy gall syndrome induced byRhodococcus fascians

Abstract: The Actinomycete Rhodococcus fascians causes the leafy gall syndrome, an infectious plant disease that affects a wide range of plants, primarily dicotyledonous herbs. The syndrome is associated with delayed senescence, loss of apical dominance, activation of dormant axillary meristems, and formation of multiple inflorescences, leading to a stunted and bushy plant appearance. A major breakthrough in the elucidation of the virulence strategy of this pathogen was the discovery of a linear virulence plasmid, pFiD1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 49 publications
0
29
1
Order By: Relevance
“…Nevertheless, whether bacterial MeCKs are transported or metabolized into corresponding conjugates requires further investigation. It is interesting to note that previous studies reported the accumulation of CK-methylthio derivatives in Arabidopsis after R. fascians infection as well as in R. fascians culture (Pertry et al, , 2010Stes et al, 2013). However, in our study, these CK derivatives were below the detection limit in the recombinant E. coli cultures expressing mts and fas4 as well as in the R. fascians-infected tobacco plants.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Nevertheless, whether bacterial MeCKs are transported or metabolized into corresponding conjugates requires further investigation. It is interesting to note that previous studies reported the accumulation of CK-methylthio derivatives in Arabidopsis after R. fascians infection as well as in R. fascians culture (Pertry et al, , 2010Stes et al, 2013). However, in our study, these CK derivatives were below the detection limit in the recombinant E. coli cultures expressing mts and fas4 as well as in the R. fascians-infected tobacco plants.…”
Section: Discussioncontrasting
confidence: 70%
“…fas4 encodes IPT that catalyzes the rate-limiting step of CK biosynthesis and is vital for virulence (Stes et al, 2013). Interestingly, two methyltransferase-like genes are present upstream of the fas gene, whose functions have been unknown.…”
mentioning
confidence: 99%
“…Extensive epiphytic growth precedes intercellular invasion through stomata. R. fascians causes various effects in its hosts, including leaf deformation and formation of witches' broom, fasciations, and leafy galls (517,519). The symptoms are caused by the hyperinduction of shoots through activation of dormant axillary meristems and de novo meristem formation, probably as the result of elaborate manipulation of host hormone balances and pathogen-derived auxins and cytokinins (520,521).…”
Section: Interactions Between Actinobacteria and Plantsmentioning
confidence: 99%
“…Other common plant pathogens fall within the Microbacteriaceae family, including Leifsonia xyli , which is the cause of ratoon stunting disease in sugarcane, and Clavibacter michiganensis , which infects xylem and causes plant wilting in alfalfa, corn, tomato, and potato (21, 47). Finally, leafy gall syndrome, which infects a wide range of dicotyledonous herbaceous plants, is caused by Rhodococcus fascians (128, 129). …”
Section: Ecology Of Actinobacteriamentioning
confidence: 99%